Village and City Geography: Analysis of Potential and Distribution of Village Services in Pisak Village, Tujuh Belas District - Febrianda, Rifky Eka; Anasi, Putri Tipa; Marshanda, Lhea; Stefanny, Stefanny; Mirawati, Agustina; Christanto, Ludovicus Manditya Hari (Universitas Tanjungpura, 2025)
This study aims to analyse the geographical characteristics, local potential, and distribution of public services in Pisak Village, Tujuh Belas Sub-district, Bengkayang Regency, West Kalimantan. The research employs a qualitative descriptive approach with field observation methods to describe spatial and social phenomena within the village. Primary data were obtained through in-depth interviews with the village head and direct observation using Avenza Map to plot the distribution of facilities, while secondary data were collected from village administrative documents and spatial maps. Data analysis was conducted using the interactive model, including data reduction, presentation, and conclusion drawing. The results show that Pisak Village possesses significant potential in agriculture and tourism. Around 90% of the population works in agriculture, producing dryland rice, vegetables, and palm oil, while its natural attractions, such as the Pisak River and traditional Nyaban’k ritual, highlight the village’s cultural richness. The village's highland location contributes to a cool climate and stable water resources that support agricultural sustainability. Socially, the community maintains strong kinship ties, cooperation, and traditional values. Public facilities, including education, health, and social infrastructure, are evenly distributed across the four hamlets, with the main service centre located in Segiring Hamlet. Spatial analysis indicates that these facilities are well distributed and accessible, supporting balanced rural development. However, challenges remain in human resource development, particularly limited access to secondary education and low economic diversification, which cause dependence on traditional farming. Therefore, improving education and training opportunities is essential to enhance community capacity and achieve sustainable village development. Overall, the study concludes that geographical conditions, local potential, and spatial distribution of services are interrelated and form the basis for inclusive and equitable rural planning in Pisak Village.